A Microcomputer-Based Medical Decision Aid for Ambulatory Care - Weaver, Alfred C. (1980)
MEDIC is a microcomputer-based medical decision aid for ambulatory care. It models patient state of health using decision analysis theory and Bayesian mathematics. MEDIC can interrogate patient history, calculate a probabilistic state of health, optimally select laboratory tests based on expected information flow, update patient state of health based on test results, and in addition allows the practitioner to partition the state space for hypothesis confirmation. The aid is now functional for the prototypical complaint diarrhea.